2009
DOI: 10.1007/s10530-009-9557-6
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and dynamics of Procambarus clarkii (Girard, 1852) in a Mediterranean brackish wetland (Central Italy)

Abstract: In 2006 an unusual find of Procambarus clarkii, today considered one of the most dangerous exotic crayfish, was made within the preserved brackish Mediterranean biotope ''Palude di Torre Flavia'' (Rome, Italy). Here the investigation on the population structure and dynamics of P. clarkii inhabiting this brackish wetland is presented in an attempt to describe the life history pattern in this type of habitat. The present study showed that this species has a lower growth rate and higher longevity than other studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 34 publications
(65 reference statements)
11
51
1
1
Order By: Relevance
“…The dataset of our study exceeded the minimum of 200 specimens suggested by France et al (1991) and the estimated life-history parameters are in good accordance with previous studies on white-clawed crayfish (cf. Scalici et al, 2010). In particular, the obtained growth performance indexes were identical to the values reported by other studies (Table III), which indicates that our growth parameter estimates are not biased (Pauly and Munro, 1984).…”
Section: > Growth and Life Historysupporting
confidence: 87%
See 4 more Smart Citations
“…The dataset of our study exceeded the minimum of 200 specimens suggested by France et al (1991) and the estimated life-history parameters are in good accordance with previous studies on white-clawed crayfish (cf. Scalici et al, 2010). In particular, the obtained growth performance indexes were identical to the values reported by other studies (Table III), which indicates that our growth parameter estimates are not biased (Pauly and Munro, 1984).…”
Section: > Growth and Life Historysupporting
confidence: 87%
“…To estimate life-history traits, growth was described using the Von Bertalanffy's Growth Function (VBGF), adjusted for seasonal growth in summer and no growth in winter (Pauly and Morgan, 1987;Scalici et al, 2010;Ghia et al, 2015):…”
Section: > Growth and Life-history Traitsmentioning
confidence: 99%
See 3 more Smart Citations